The Influence Of Influencers On Purchasing Luxcrime Products (Case Study Of Students In Medan City) - Rawi, Nadya Tasya; Tambunan, Sarah Rouli (Program Pascasarjana UIN Sumatera Utara, 2025)
Luxcrime is a local cosmetic brand produced by PT Luxury Cantika Indonesia. Its flagship product is Luxcrime Two Way Cake which is a combination of powder and foundation that merge into one. Luxcrime Two Way Cake has won the most sales, beating foreign brands. One of the factors that influence purchasing decisions is influencer recommendations. Luxcrime brand endorses an Indonesian beauty influencer named Tasya Farasya to review Luxcrime products on her social media accounts. The purpose of this study was to determine the effect of influencers on purchasing decisions for Luxcrime products among students in Medan city. The type of research used is quantitative research. The data collection technique used in this research is the questionnaire method and uses a Likert scale. The sample in this study were 100 respondents, namely students in Medan city who know Luxcrime Two Way Cake products, have bought Luxcrime Two Way Cake, and have watched Luxcrime Two Way Cake reviews on Tasya Farasya's social media accounts. The sampling method used is accidental sampling. The analysis method used is simple regression with hypothesis testing using the SPSS 23 program. The results of simple regression calculations explain that the independent variable influencer has a positive effect on the dependent variable of purchasing decisions. Then based on hypothesis testing, it is proven that H1 accepted.